Comparative study of coagulation and thrombin generation in the portal and jugular plasma of patients with cirrhosis - Delahousse, Bénédicte; Labat-Debelleix, Valérie; Decalonne, Loic; d’Alteroche, Louis; Perarnau, Jean-Marc; Gruel, Yves (Thrombosis and Haemostasis, 2010)
Portal vein thromboses are frequent in cirrhotic patients and may be favoured by hypercoagulability in the splanchnic venous system. The coagulation balance and thrombin generation (TG) were evaluated in platelet-free plasma obtained from portal and systemic blood samples in 28 cirrhotic patients while undergoing transjugular intrahepatic porto-systemic shunt. TG assay (TGA) was performed with all samples from cirrhotic patients and with plasma samples from 14 healthy controls, with varying concentrations of tissue factor and phospholipids, with or without thrombomodulin. Screening tests and specific assays were also performed and activated partial thromboplastin time was shorter in portal plasma samples with higher FVIII and lower protein C levels, well correlated with Child-Pugh scores, and higher D-dimers and F1+2 levels However, all TGA parameters were similar in portal and jugular samples, possibly due in part to similar concentrations of factor II and antithrombin in these two sites of plasma sampling. TGA showed lower thrombin peaks and endogenous thrombin potential values in cirrhotic plasma compared to those of healthy controls. Importantly, a resistance to thrombomodulin that well correlated with factor VIII and PC levels, was evidenced in all samples from patients with cirrhosis, and was more significant in those from severely affected cases. This study therefore supports the existence of a relative hypercoagulability in the portal vein of cirrhotic patients that is likely due to protein C/S deficiency and to high FVIII levels.
Keywords: Cirrhosis; thrombin generation assay; liver disease; coagulation